A COMPARATIVE ANALYSIS OF STUDENT ENGAGEMENT IN FORMAL AND SUPPLEMENTAL ENGLISH CLASSES AT PONDOK PESANTREN AS-SALAFIYAH SUMBER DUKO PAMEKASAN - Eriyanto, Eriyanto; Mistar, Junaidi; Heriyawati, Fita Dwi (Abjadia : International Journal of Education, 2024)
Given the unique and immersive English language environment at Pondok Pesantren and MA As-Salafiyah Sumber Duko Pameksan , a comparative analysis of student engagement in both formal (classroom-based) and supplemental (extracurricular) English classes becomes essential.This research eventually aims to address the strengths and weaknesses of formal English instruction in fostering language proficiency among students at MA As-Salafiyah is, to what extent students actively engage with the content and teaching methods employed in formal English classes and how students perceive the value and impact of participating in extracurricular language activities.The study employed a qualitative research method with case study analysis., The findings reveal a complex interplay of factors influencing language learning in this context. While formal instruction, grounded in linguistic theory and structured lesson plans, provides a solid foundation, it faces challenges related to time constraints, limited real-world application, and student engagement. Conversely, extracurricular language activities, such as English camps, clubs, and competitions, are highly valued by both students and teachers for their immersive nature, focus on practical communication, and positive impact on motivation and confidence. These activities foster a sense of community among learners and complement formal instruction by providing opportunities for authentic language use and personal growth.The study concludes that a holistic approach that integrates formal instruction with engaging extracurricular activities, supported by adequate resources and a positive learning environment, can optimize language learning outcomes and foster a positive learning experience for students.